Keanekaragaman Pakan Lebah Madu Apis cerana di Hutan Rakyat Berdasarkan Karakteristik Polen (Diversity of Apis cerana Honey Bee Foraging Plants in Community Forests Based on Pollen Characteristics) - Khozanah Syifa; Noor Farikhah Haneda; Eva Rachmawati (Jurnal Penelitian Hutan Tanaman, 2023)
AbstractHoneybees are very important pollinating insects because their pollination activity can improve fruit quality and productivity. Pollen is a male gametophyte of a plant with the reproductive function to fertilize the ovule. Honeybees use pollencollected from various plants as a source of food, especially protein. Pollen contains different types of amino acids that honey bees using it to synthesize food. This study aims to investigate the source of pollen from the honeybee colony of Apis cerana collecting food based on pollen characteristics. Pollen samples were taken from the hind limbs of worker bees and honeycomb of Apis cerana honey bee colonies at the apiary of KTH Wana Karya Tani Sejahtera in Buana Sakti Village, Buana Sakti Village, Batanghari District, East Lampung Regency, Lampung Province. Pollen recognition was performed by identifying their characteristics through the pollen aperture, pollen based on the polar and equatorial, ornamentation, and pollen size. The research showed seven plant species were used by honeybees as a food source for pollen. Each species comes from a different family. The type of pollen aperture found varies according to plant species. Types of pollen aperture 1-colpate and pastorate are commonly found in pollen from hind legs. This type of aperture was also found in hive-stored pollen. The dominant types of pollen found in leg and nest pollen came from C. nucifera and A. mangium species.Key words: Bee, feed source, pollen characteristicsAbstrakLebah madu termasuk serangga penyerbuk yang sangat penting, dimana aktivitas penyerbukannya dapat meningkatkan kualitas dan produktifitas buah. Polen merupakan benih jantan tumbuhan yang berfungsi untuk pembuahan. Lebah madu memanfaatkan polen sebagai pakan, khususnya protein. Polen mengandung jenis asam amino yang berbeda bagi lebah berfungsi untuk sintesis makanan. Penelitian ini bertujuan untuk mengidentifikasi polen yang menjadi sumber pakan lebah madu berdasarkan karakteristik dan asal tumbuhannya. Sampel polen diambil dari tungkai dan sarang lebah di apiary Apis cerana di KTH Wana Karya Tani Sejahtera di Desa Buana Sakti, Kelurahan Buana Sakti, Kecamatan Batanghari, Kabupaten Lampung Timur, Provinsi Lampung. Identifikasi polen dilakukan dengan memperhatikan karakter aperture polen, bentuk polen berdasarkan polar dan ekuatorial, ornamentasi eksin serta ukuran polen. Hasil penelitian menunjukkan terdapat tujuh spesies tumbuhan yang dimanfaatkan lebah madu sebagai sumber polen. Masing-masing spesies berasal dari famili yang berbeda. Tipe aperture polen ditemukan berbeda-beda sesuai dengan jenis tanaman. Tipe polen 1-colpate dan pantoporate banyak ditemukan pada polen tungkai. Jenis aperture tersebut juga ditemukan pada polen sarang. Jenis polen yang dominan ditemukan pada polen tungkai dan polen sarang berasal dari spesies C. nucifera dan A. mangium.Kata kunci: Lebah madu, karakteristik polen, sumber pakan